A Qualitative Evaluation of the Knowledge Levels of Nurses Regarding Informatics and Health Informatics: The Case of Atatürk Training and Research Hospital. - Çetin, Sibel; Ergün, Mehmet Ali; Tekindal, Mustafa Agah; Tekindal, Benian; Tekindal, Melike (International Journal of Caring Sciences)
Aim: to examine the information technology and information management systems use of nurses working at Ankara Atatürk Training and Research Hospital. Method: A qualitative research with purposeful sampling method was used. 31 of 430 nurses working at Ankara Atatürk Training and Research Hospital between 15th of December 2010 and 10th of January 2011 participated in the study. Nurse Interview Form was prepared to collect data. Interviews were tape recorded, transcribed, and classified thematically. Data were analyzed through content analysis and the analysis yielded four main themes: "computer use, access, and obstacles", "use of information technology and its necessity for nurses", "health information systems", and "education for information technology". Results: Regarding computer use level, 25.81% of the nurses said, "sufficient"; 45.18% said, "medium"; and 29.03% said, "slightly sufficient". As to the programs used, 12.90% of the nurses used "Hospital Information Management System (HIMS) and the Internet"; 74.19% used "HIMS and at least two programs"; and 6.45% used "MS Word, Excel, PowerPoint, and the Internet apart from HIMS". A great majority of the nurses think that computer use in work brings benefits. However, they think that computer use is currently limited due to lack of education, lack of computer, Internet access problems, and workload. Recommendations: Medical establishments should firstly focus on lack of education about the use of information technology among nurses. In addition, they should urgently deal with problems such as workload, the number of computers, Internet access, and technical support. Moreover, nursing training institutions should ascertain their deficiencies and rearrange their curricula.